Africa Bible commentary series : 2 Peter and Jude (Carlisle, Cumbri, UK, HippoBooks, 2018)
Shorter books in the Bible like 2 Peter and Jude are often overlooked by believers as they flick through pages of Scripture. Furthermore, because these two books deal with the unpopular theme of God's judgement they end up being further neglected in the believer's life and understanding of Scripture. Yet the evils these authors speak about are still very much present in the church in Africa, and are no less deserving of judgment today. But these books also bear glorious testimony to God's power to preserve his people, and encourage us to stay steadfast and conform to the pattern of holiness in which we have been rooted. The landmark Africa Bible Commentary compiled the scholarship of seventy African scholars in one volume. Now, the Africa Bible Commentary Series provides deeper insights into each biblical book, explaining the meaning of Scripture in smaller, separate volumes. The series emphasizes the relevance of biblical concepts for the life of the local church and the case studies and African illustrations accomplish this in ways that mere explanations cannot. In addition, each commentary is divided into sermon units for easy use in developing a preaching series on the biblical books and includes discussion questions to assist further study.
Keywords: Bible.-- Jude; Bible.-- Jude, Commentaries; Bible.- Peter, 2nd Commentaries; Criticism, interpretation, etc